2016
DOI: 10.1093/ntr/ntw132
|View full text |Cite
|
Sign up to set email alerts
|

Time-to-Pregnancy Associated With Couples’ Use of Tobacco Products

Abstract: Introduction: Previous studies suggest female smoking increases time-to-pregnancy (TTP), a couple-dependent reproductive outcome, while associations with male smoking are more ambiguous. Furthermore, despite small increases in smokeless tobacco use in the United States, no prior study has evaluated TTP among smokeless tobacco users. Methods: Using population-based sampling in 16 counties in Michigan and Texas, 501 couples discontinuing contraception to become pregnant were followed until positive pregnancy tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 43 publications
(39 reference statements)
0
20
3
Order By: Relevance
“…Besides, decreased ovarian function and reduced ovarian reserve may also be possible consequences of smoking, as shown by lower anti-Müllerian hormone (AMH) concentrations in smokers compared with non-smokers (Freour et al, 2008). Studies included in this review confirm these hypotheses by showing statistically significant negative associations of smoking especially with fecundity parameters (Laurent et al, 1992;Axmon et al, 2000;Radin et al, 2014), although a significantly prolonged time to pregnancy was found in only two out of six studies included in this review (Hull et al, 2000;Sapra et al, 2016).…”
Section: Smokingmentioning
confidence: 52%
See 2 more Smart Citations
“…Besides, decreased ovarian function and reduced ovarian reserve may also be possible consequences of smoking, as shown by lower anti-Müllerian hormone (AMH) concentrations in smokers compared with non-smokers (Freour et al, 2008). Studies included in this review confirm these hypotheses by showing statistically significant negative associations of smoking especially with fecundity parameters (Laurent et al, 1992;Axmon et al, 2000;Radin et al, 2014), although a significantly prolonged time to pregnancy was found in only two out of six studies included in this review (Hull et al, 2000;Sapra et al, 2016).…”
Section: Smokingmentioning
confidence: 52%
“…The characteristics of the included studies are shown in TABLE 1. Thirty-five studies were identified as prospective (Laurent et al, 1992;Florack et al, 1994;Windham et al, 1997;Caan and C. P. Quesenberry, 1998;Hakim et al, 1998;Jensen et al, 1998;Hull et al, 2000;Kesmodel et al, 2002;Arakawa et al, 2006;Law et al, 2007;Strandberg-Larsen et al, 2008;Bakker et al, 2010;Mook-Kanamori et al, 2010;Prabhu et al, 2010;Wise et al, 2010;Hatch et al, 2012;Mutsaerts et al, 2012;Wise et al, 2012;Bouwland-Both et al, 2013;van Uitert et al, 2013b;Wise et al, 2013, Gaskins et al, 2014bHahn et al, 2014;Radin et al, 2014;Van Uitert et al, 2014;Andersen et al, 2015;Hahn et al, 2015;Cueto et al, 2016;Gaskins et al, 2016;McKinnon et al, 2016;Sapra et al, 2016;Wesselink et al, 2016;Zhou et al, 2016;Parisi et al, 2017), six as retrospective cohort studies (Bolúmar et al, 1997, Axmon et al, 2000, Juhl et al, 2001, Juhl et al, 2003, Axmon et al, 20...…”
Section: Results Of Search and Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to pregnancy, the prevalence of partners who smoked was slightly higher than the prevalence of women who smoked, but in contrast to their female counterparts they did not quit smoking during the pregnancy. Whereas tobacco use in pregnancy has been vastly analysed, few studies present data about the prevalence of partners who smoke during pregnancy (15% in Minnesota, EE.UU and 30% in Galicia, north of Spain), or on the prevalence of partners that quit smoking (8.5% in Barcelona, Spain; 11.1% in Ashford, UK, and in Barcelona and Menorca, Spain). Recently, from a qualitative point of view, Fleming et al focused on barriers and facilitators to smoking cessation experienced by women's partners.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that partner smoking affects the offspring, leading to small for gestational age, fetal deaths, and birth defects . Moreover, the prevalence of tobacco use among partners and smoking cessation of the partners is rarely considered . To our knowledge, no studies have shed light on active smoking and passive smoking habits throughout the three trimesters of pregnancy.…”
Section: Introductionmentioning
confidence: 99%